Corporate Voluntarism and Human Rights: The Adequacy and Effectiveness of Voluntary Self-Regulation Regimes - Simons, Penelope (Relations industrielles / Industrial Relations, 2004)
In response to increasing public concern over the accountability of transnational corporations (TNCs) for violations of human rights in the states in which they operate, governments, corporations and NGOs have promoted the development and implementation of voluntary self-regulatory regimes. However, TNC practices under these regimes call into question their adequacy and effectiveness in preventing complicity in egregious violations of human rights by corporations operating in conflict zones and repressive regimes. This article reviews and assesses the language, human rights content and compliance mechanisms of the voluntary policies and/or codes developed by a number of corporations, industry groups, intergovernmental organizations and multistakeholder initiatives, as well as associated corporate practices. The analysis shows that these voluntary regimes are flawed and inadequate, and therefore unable to ensure that TNCs are not complicit in human rights violations in their extra-territorial activities.